Epigenetic regulations in the IFNγ signalling pathway: IFNγ-mediated MHC class I upregulation on tumour cells is associated with DNA demethylation of antigen-presenting machinery genes - Vlková, Veronika; Štěpánek, Ivan; Hrušková, Veronika; Šenigl, Filip; Mayerová, Veronika; Šrámek, Martin; Šímová, Jana; Bieblová, Jana; Indrová, Marie; Hejhal, Tomáš; Dérian, Nicolas; Klatzmann, David; et al. (Oncotarget, 2014)
Downregulation of MHC class I expression on tumour cells, a common mechanism by which tumour cells can escape from specific immune responses, can be associated with coordinated silencing of antigen-presenting machinery genes. The expression of these genes can be restored by IFNγ. In this study we documented association of DNA demethylation of selected antigen-presenting machinery genes located in the MHC genomic locus (TAP-1, TAP-2, LMP-2, LMP-7) upon IFNγ treatment with MHC class I upregulation on tumour cells in several MHC class I-deficient murine tumour cell lines (TC-1/A9, TRAMP-C2, MK16 and MC15). Our data also documented higher methylation levels in these genes in TC-1/A9 cells, as compared to their parental MHC class I-positive TC-1 cells. IFNγ-mediated DNA demethylation was relatively fast in comparison with demethylation induced by DNA methyltransferase inhibitor 5-azacytidine, and associated with increased histone H3 acetylation in the promoter regions of APM genes. Comparative transcriptome analysis in distinct MHC class I-deficient cell lines upon their treatment with either IFNγ or epigenetic agents revealed that a set of genes, significantly enriched for the antigen presentation pathway, was regulated in the same manner. Our data demonstrate that IFNγ acts as an epigenetic modifier when upregulating the expression of antigen-presenting machinery genes.
Keywords: transfekce; down regulace; Gene Expression Regulation, Neoplastic; DNA Methylation; Interferon-gamma; prezentace antigenu; Up-Regulation; Fibrosarcoma; metylace DNA; Transfection; regulace genové exprese u nádorů; epigeneze genetická; signální transdukce; upregulace; interferon gama; Signal Transduction; Animals; Down-Regulation; zvířata; fibrosarkom; myši inbrední C57BL; nádorové buňky kultivované; myši; Mice, Inbred C57BL; Tumor Cells, Cultured; Antigen Presentation; Mice; geny MHC třídy I; Genes, MHC Class I; Epigenesis, Genetic